2020
DOI: 10.21203/rs.3.rs-28670/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Policy Decisions and Response to Fight 2019 Novel Coronavirus Disease in Uganda: A review of Attributes, Comprehensiveness and Implications to Improve Resilience to Future Pandemics

Abstract: Uganda experiences recurrent epidemics. However, policies enacted to prevent or prepare for future epidemics remain unclear. This paper reviews policies that are shaping responses to the Coronavirus disease (COVID-19) in Uganda. An integrative systematic review approach using the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) was adopted. Databases including organizational websites, bibliographical databases, and newsletters were searched for records on policies addressing response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…That led to a full a lock down on 30th March which involved an immediate ban on private and public transport, school closures and restrictions on gatherings. Commentators have suggested the need for a full lockdown derived from Uganda’s geographical position as a landlocked country (Kiwanuka et al, 2019). A travel ban on air, water and roads was enacted, social distancing and preventive isolation measures were also fully implemented (Presidential address 1).…”
Section: The Ugandan Justice System and The Pandemicmentioning
confidence: 99%
“…That led to a full a lock down on 30th March which involved an immediate ban on private and public transport, school closures and restrictions on gatherings. Commentators have suggested the need for a full lockdown derived from Uganda’s geographical position as a landlocked country (Kiwanuka et al, 2019). A travel ban on air, water and roads was enacted, social distancing and preventive isolation measures were also fully implemented (Presidential address 1).…”
Section: The Ugandan Justice System and The Pandemicmentioning
confidence: 99%
“…Through a collaborative discussion regarding the topics of evidence syntheses, the following research priorities are recommended: Governance: This study found only 3 evidence syntheses that discussed leadership, policy, and governance mechanisms during the Covid-19 pandemic. 8 – 10 Concentrated attention is required on this topic, particularly from the perspective of how to adapt leadership and governance mechanisms to ensure that institutional and national responses to pandemics are rapid, effective, and appropriate. Populations: Multiple evidence syntheses included in this study investigated the impact of Covid-19 on the lives and mental well-being of a variety of populations.…”
Section: Discussionmentioning
confidence: 99%
“…Governance: This study found only three evidence syntheses that discussed leadership, policy, and governance mechanisms during the COVID-19 pandemic. [8][9][10] Concerted attention is required on this topic, particularly from the perspective of how to adapt leadership and governance mechanisms to ensure that institutional and national responses to pandemics are rapid, effective, and appropriate.…”
Section: Research Prioritiesmentioning
confidence: 99%
“…Uganda is also not exception, having registered her first COVID-19 positive case on the 31 st of March 2020 (Kiwanuka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%